Contemporary Anti-Retroviral Drugs (ARVDs) Disrupt Follicular Development in Female Wistar Rats - Ohihoin AG; Ohihoin EN; Ujomu I; Bakare A; Olanrewaju O; Okafor A; Ojetunde M; Ayoola JB; Aina O; Ajibaye O; Taylor-Robinson SD (Dove Medical Press, 2023)
Aigbe Gregory Ohihoin,1 Esther Ngozi Ohihoin,2 Ifeoma Ujomu,3 Airat Bakare,4 Oladeji Olanrewaju,2 Arinze Okafor,5 Mercy Ojetunde,1 Joy Boluwatife Ayoola,6 Oluwagbemiga Aina,7 Olusola Ajibaye,7 Simon D Taylor-Robinson8 1Clinical Sciences Department, Nigerian Institute of Medical Research (NIMR), Lagos, Nigeria; 2Research Unit, HICI Healthcare Limited, Lagos, Nigeria; 3University Hospitals of Leicester NHS Trust, Leicester, UK; 4College of Medicine, University of Lagos, Lagos, Nigeria; 5School of Life Sciences, University of Nottingham, Nottingham, UK; 6Central Research Laboratory, Nigerian Institute of Medical Research (NIMR), Lagos, Nigeria; 7Biochemistry and Nutrition Department, Nigerian Institute of Medical Research (NIMR), Lagos, Nigeria; 8Department of Surgery and Cancer, Imperial College London, London, UKCorrespondence: Aigbe Gregory Ohihoin, Clinical Sciences Department, Nigerian Institute of Medical Research (NIMR), Yaba, Lagos, Nigeria, Tel +2348035604697, Email aigbe.ohihoin@yahoo.comIntroduction: There are genuine concerns that long-term use of anti-retroviral drugs may be associated with reproductive complications in females. This study aimed to ascertain the effect of highly active anti-retroviral drugs on the ovarian reserve and reproductive potential of female Wistar rats and by extension to HIV-positive human females.Methods: A total of 25 female Wistar rats, weighing between 140g and 162g, were randomly allotted into non-intervention and intervention groups, receiving the anti-retroviral drugs, Efavirenz (EFV), Tenofovir Disoproxil Fumarate (TDF), Lamivudine (3TC), and a fixed-dose combination (FDC). The dosage was administered orally at 8 am daily for 4 weeks. Serum concentrations of anti-Mullerian hormone (AMH), follicle-stimulating hormone (FSH), luteinising hormone (LH), and estradiol were measured using standard biochemical techniques (ELISA). Follicular counts were made on fixed ovarian tissue from the sacrificed rats.Results: The mean AMH level for the control group and the EFV, TDF, 3TC, and FDC groups were 11.20, 6.75, 7.30, 8.27, and 6.60 pmol/L, respectively. The EFV and FDC groups had the lowest AMH, compared to the other groups, but there was no statistically significant difference in AMH across the groups. The mean count of antral follicles was significantly lower in the group that received EFV when compared to the other groups. The corpus luteal count was significantly higher in the control group than in the intervention groups.Conclusion: The study demonstrated a disruption in the reproductive hormones of female Wistar rats receiving anti-retroviral regimens containing EFV. Clinical studies are required to determine if these changes are seen in women receiving EFV-based treatment, as this may compromise reproductive function and predispose them to early menopause.Keywords: highly active anti-retroviral therapy, HAART, estradiol, anti-Mullerian hormone, human immunodeficiency virus, HIV, Nigeria